Comparative Effectiveness of Luliconazole, Sertaconazole, and Terbinafine for Tinea Corporis and Tinea Cruris: A Systematic Review - Ni Luh Putu Eka Widya Ananta Putri; Marisa Syavitri Dilaga (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
Dermatophytosis (tinea corporis and tinea cruris) is a superficial fungal infection with a high prevalence in tropical regions. The WHO has reported cases of resistance to antifungal treatments. Topical antifungals from the allylamine (terbinafine) and azole (sertaconazole and luliconazole) classes are widely used; however, evidence regarding their comparative head-to-head effectiveness is inconsistent and has not yet been systematically synthesized with rigorous methodological quality assessment. This study aimed to evaluate and compare the clinical effectiveness, mycological cure rates, cost-effectiveness, and safety of topical terbinafine, sertaconazole, and luliconazole for tinea corporis and tinea cruris through a systematic review. A literature search was conducted using Publish or Perish across Google Scholar (n=200) and PubMed (n=16), yielding 216 articles. Following deduplication via Covidence (17 duplicates), title/abstract screening, and full-text review, nine studies met the final eligibility criteria. Methodological quality was assessed using the JBI Critical Appraisal Checklist for RCTs (13 items); six studies scoring >50% were included in the narrative synthesis. Results showed that comparisons between sertaconazole and terbinafine (four studies) consistently demonstrated equivalent effectiveness, although one high-quality study reported sertaconazole to be superior in terms of rapid relief from pruritus and achieving mycological cure. In one study of moderate quality, luliconazole demonstrated a significantly greater reduction in symptom scores compared to terbinafine. Sertaconazole showed higher clinical effectiveness than luliconazole, yet luliconazole was superior in terms of cost-effectiveness in one moderate-quality study. All three drugs were reported to be safe and well-tolerated. In conclusion, the three antifungal agents demonstrate generally comparable effectiveness in the management of tinea corporis and tinea cruris infections, although sertaconazole and luliconazole tend to outperform terbinafine in certain parameters across some studies.